A modified carbon fiber and its preparation method and application

By chemically grafting carboxylated MWCNTS or graphene oxide on the surface of carbon fiber, combined with the steric steric hindrance effect of PVP, the problem of poor interface between carbon fiber and nylon 66 resin is solved, and the mechanical properties and interface bonding strength of the composite material are significantly improved.

CN119352292BActive Publication Date: 2025-04-18DONGHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411884362.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18
Estimated Expiration
2044-12-20

Smart Images

  • Figure CN119352292B_ABST
    Figure CN119352292B_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of carbon fiber modification, and relates to a modified carbon fiber and a preparation method and application thereof, wherein the preparation method is to mix pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material uniformly until KH550, PVP, and carbon material are gathered on the surface of pre-oxidized carbon fiber, first separate solid and liquid, then add water to the liquid and mix uniformly, then mix solid and liquid, then heat at 50-80°C for 30-75min, and then remove the carbon material physically adsorbed on the surface of pre-oxidized carbon fiber to obtain modified carbon fiber; the tensile strength of the obtained modified carbon fiber is 5.0-5.3GPa, and the micro-debonding strength of the modified carbon fiber and PA66 resin is 58-61MPa; the application is to prepare composite materials by compounding it with PA66 resin. The preparation method of the present invention has a simple flow and a short cycle, does not involve a strong acid and alkali environment, and has very little damage to the strength of the fiber monofilament itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon fiber modification, and specifically relates to a modified carbon fiber and a preparation method and application thereof. Background Art

[0002] Carbon fiber has excellent properties such as high specific strength, high specific modulus, low thermal expansion coefficient, high electrical conductivity and thermal conductivity, and is generally used as a reinforcement for advanced composite materials. Carbon fiber reinforced thermoplastic composites have the advantages of short molding cycle, easy processing, excellent mechanical properties and recyclability, and have gradually become one of the research hotspots of carbon fiber composites.

[0003] However, due to the chemical inertness of the carbon fiber surface, when preparing carbon fiber / nylon 66 (CF / PA66) composite materials, the wettability between CF and PA66 resin is poor, and debonding is easily produced at the weak interface during use, which will affect the mechanical properties of the CF / PA66 composite material. Therefore, it is necessary to further improve the interfacial bonding strength of the CF / PA66 composite material by surface treatment of the carbon fiber, thereby improving its mechanical properties.

[0004] Patent application CN103409985A discloses a method for preparing carbon nanotube-loaded carbon fibers, comprising the following steps:

[0005] (1) Oxidation treatment of carbon nanotubes; (2) Grafting treatment on the surface of carbon nanotubes; adding the oxidized carbon nanotubes and 3-aminopropyltriethoxysilane coupling agent to an ethanol solution, stirring, filtering, and drying to obtain grafted carbon nanotubes; (3) Oxidation treatment of carbon fibers; (4) Carbon nanotube-loaded carbon fiber treatment; adding carbon fibers and carbon nanotubes to an acetone solution for ultrasonic dispersion, adding alkali solution until the solution is transparent, taking out the carbon nanotube-loaded carbon fibers, and drying to obtain carbon nanotube-loaded carbon fibers. The preparation method of this patent requires first grafting 3-aminopropyltriethoxysilane on the surface of carbon nanotubes and drying to obtain modified carbon nanotubes, and then grafting them onto the surface of carbon fibers. However, the preparation method of this patent has many problems, such as a long preparation process cycle, and the use of acetone, KOH and other chemicals in the grafting process. Strong acids and alkalis will cause varying degrees of damage to the strength of the carbon fibers themselves.

[0006] Therefore, it is necessary to propose a new method for preparing modified carbon fiber in order to solve the problems in the preparation process of the modified carbon fiber mentioned above. Summary of the invention

[0007] The purpose of the present invention is to solve the problems in the prior art and to provide a modified carbon fiber and a preparation method and application thereof.

[0008] To achieve the above object, the present invention adopts the following technical solutions:

[0009] A carbon fiber modification method comprises the following steps: uniformly mixing pre-oxidized carbon fiber, ethanol, KH550, PVP and carbon material until KH550, PVP and carbon material are gathered on the surface of the pre-oxidized carbon fiber, firstly separating solid from liquid (the purpose is to prevent KH550, PVP and carbon material gathered on the surface of the pre-oxidized carbon fiber from falling off in the next mixing process), then adding water to the liquid and mixing uniformly, then mixing the solid and liquid, and then heating at 50-80°C for 30-75min (KH550 undergoes hydrolysis reaction during this process), and then removing the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber (ultrasonication for 30-75min, washing and drying at 60-90°C) to obtain modified carbon fiber, wherein the pre-oxidized carbon fiber is an oxidized carbon fiber, and the carbon material is carboxylated MWCNTS or graphene oxide.

[0010] As the preferred technical solution:

[0011] In the carbon fiber modification method as described above, the volume ratio of ethanol to KH550 is 5-10:1, the ratio of the mass of carbon material to the total volume of ethanol, KH550, PVP and carbon material is 1-5 mg:1 mL, the ratio of the mass of PVP to the total volume of ethanol, KH550, PVP and carbon material is 2-8 mg:1 mL, and the mass ratio of pre-oxidized carbon fiber to carbon material is 2-8:1.

[0012] A carbon fiber modification method as described above, wherein the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material are uniformly mixed until KH550, PVP, and carbon material are aggregated on the surface of the pre-oxidized carbon fiber, refers to adding the pre-oxidized carbon fiber to a mixture of ethanol, KH550, PVP, and carbon material, first ultrasonicating for 30-75 minutes, and then heating at 50-80°C for 30-75 minutes.

[0013] In the carbon fiber modification method as described above, the ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:0.5-2.

[0014] In the carbon fiber modification method as described above, adding water to the liquid and mixing it evenly refers to adding water to the liquid and then ultrasonicating it for 30-75 minutes.

[0015] A carbon fiber modification method as described above, the preparation process of pre-oxidized carbon fiber is: first, the carbon fiber is added to a K2S2O8 (i.e. potassium persulfate) / AgNO3 (i.e. silver nitrate) aqueous solution and heated in a water bath at 60-100°C for 45-75min, the K2S2O8 / AgNO3 aqueous solution is composed of K2S2O8, AgNO3 and water, then taken out, washed with water, and finally added to ethanol and refluxed at 90-120°C for 3-5h, taken out, and dried to obtain pre-oxidized carbon fiber, wherein the reflux is to clean the carbon fiber, and the amount of ethanol used can completely wash the carbon fiber.

[0016] In the carbon fiber modification method as described above, in the K2S2O8 / AgNO3 aqueous solution, the mass ratio of K2S2O8 to AgNO3 is 15:1-20:1, the concentration of K2S2O8 is 0.05-0.1 mol / L; the mass ratio of carbon fiber to the K2S2O8 / AgNO3 aqueous solution is 1:10-40.

[0017] A modified carbon fiber is prepared by a carbon fiber modification method as described in any one of the above items, the single-filament tensile breaking strength of the modified carbon fiber is 5.0-5.3 GPa, the single-filament tensile breaking strength of the untreated carbon fiber is 5.4-5.6 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 58-61 MPa.

[0018] The modified carbon fiber as described above is used for compounding with PA66 resin to prepare a composite material.

[0019] Principle of the invention:

[0020] The present invention utilizes PVP to simplify the grafting process of carbon fiber-KH550-carbon material, shorten the test cycle, and the whole process of the invention does not use strong acid and strong base substances, which has little effect on the strength of the carbon fiber itself, and can better improve the interfacial shear performance of the carbon fiber / PA66 composite material. The effects of PVP include: ① The hydrophobic groups on the PVP molecules can attract each other with the hydrophobic groups on the carbon material and the surface of the pre-oxidized carbon fiber, so that PVP is adsorbed on the surface of the carbon material and the pre-oxidized carbon fiber. Its steric hindrance effect can overcome the van der Waals force between the pre-oxidized carbon fiber and the carbon material, so that the carbon material is closer to the surface of the pre-oxidized carbon fiber, providing conditions for its subsequent application of KH550 grafting. ② PVP grafts the carbon material to the surface of the pre-oxidized carbon fiber. In the subsequent application process, the amide group of the PA66 resin produces a polar effect with the PVP and carbon material on the surface of the pre-oxidized carbon fiber, so that the micro-debonding strength of the modified carbon fiber and PA66 is higher.

[0021] Beneficial effects:

[0022] The present invention chemically grafts carboxylated MWCNTS or graphene oxide onto the surface of carbon fiber, so that the surface roughness of the carbon fiber is increased, the number of polar groups is increased, the contact angle is reduced, the surface energy is increased, the carbon fiber-thermoplastic resin interface can be improved, the anchoring effect of the carbon fiber in the resin matrix is ​​enhanced, the bonding performance is improved, and the total pulling power and shear bonding strength are greatly improved.

[0023] The preparation method of the present invention does not involve a strong acid or strong alkali environment, and the damage to the strength of the fiber monofilament itself is very small.

[0024] The preparation method of the invention has a simple process and a short cycle, is conducive to improving industrial production efficiency, and is suitable for industrial processing of long continuous carbon fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the surface morphology of pre-oxidized carbon fiber prepared in Example 2 of the present invention;

[0026] Figure 2 Schematic diagram of the surface morphology of the modified carbon fiber obtained in Example 3 of the present invention;

[0027] Figure 3 This is a schematic diagram of infrared spectrum comparison of carbon fiber before modification in Example 1 of the present invention;

[0028] Figure 4 It is a comparison diagram of the microsphere removal results of the carbon fiber before and after modification and PA66 in Example 1 of the present invention; in the figure, (a) is a microsphere removal diagram of the carbon fiber precursor, (b) is a microsphere removal diagram of the pre-oxidized carbon fiber, (c) is an enlarged diagram of the white frame area in (b), and (d) is a microsphere removal diagram of the modified carbon fiber;

[0029] Figure 5 This is a schematic diagram of the surface morphology of the modified carbon fiber prepared in Comparative Example 1. DETAILED DESCRIPTION

[0030] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0031] The sources of some substances in the following examples and comparative examples are as follows:

[0032] Carbon fiber: The manufacturer is Jiangsu Hengshen Co., Ltd., brand HF40;

[0033] Ethanol: analytical grade;

[0034] Carboxylated MWCNTS: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., the brand is XFM03;

[0035] Graphene oxide: The manufacturer is Jiangsu Xianfeng Nanomaterials Co., Ltd., CAS number is 7440-44-0;

[0036] It should be noted that these manufacturers and brands are only selected for the test of the embodiments, and other manufacturers and brands with the same performance on the market can be used.

[0037] The detection methods of relevant performance indicators in the following embodiments and comparative examples are as follows:

[0038] Single-filament tensile breaking strength: Referring to the method for measuring the single-filament tensile breaking strength in the prior art in this field, the AT6 single-filament fiber strength and elongation instrument of Shanghai Landing Microelectronics Research Institute was used for testing. A single carbon fiber was straightened and fixed with epoxy glue to the middle of a pre-cut paper frame. After the glue was cured, the paper frame was fixed on the test fixture to ensure the vertical state of the carbon fiber. The paper frame was cut, the tensile speed was set to 10 mm / min, and the breaking strength of the carbon fiber was recorded when it broke. The carbon fiber sample was tested 20 times to obtain the average value.

[0039] Micro-debonding strength of carbon fiber and PA66 resin: Referring to the test method of micro-debonding strength of fiber and PA66 resin in the prior art in this field, a composite material interface evaluation device (model: HM410) was used for testing; samples need to be prepared in advance before testing: the carbon fiber monofilament is fixed on the iron sheet matched with the instrument with double-sided tape, and the PA66 pellets are fixed in the spiral metal heating wire; the prepared carbon fiber sample is placed in the instrument, and after reaching the melting temperature, the PA66 is made into symmetrical microspheres and hung on the carbon fiber monofilament, and the diameter of the microspheres is controlled to be 60-80μm; the carbon fiber sample is tested 20 times and the average value is taken.

[0040] Example 1

[0041] A carbon fiber modification method, the specific steps are as follows:

[0042] (1) Raw material preparation:

[0043] Carbon fiber;

[0044] K2S2O8 / AgNO3 aqueous solution: composed of K2S2O8, AgNO3 and water, the mass ratio of K2S2O8 to AgNO3 is 15:1, and the concentration of K2S2O8 is 0.05mol / L;

[0045] Ethanol;

[0046] KH550;

[0047] PVP: degree of polymerization is 10000;

[0048] Carbon material: carboxylated MWCNTS;

[0049] (2) Preparation of pre-oxidized carbon fibers:

[0050] The carbon fiber was added to a K2S2O8 / AgNO3 aqueous solution and heated in a water bath at 100°C for 45 minutes, then taken out, washed with water, and finally added to ethanol and refluxed at 110°C for 4 hours, taken out, and dried to obtain pre-oxidized carbon fiber;

[0051] Among them, the mass ratio of carbon fiber to K2S2O8 / AgNO3 aqueous solution is 1:10;

[0052] (3) Preparation of modified carbon fiber:

[0053] (3.1) Pre-oxidized carbon fiber was added to a mixture of ethanol, KH550, PVP, and carbon material, first ultrasonicated for 30 min, and then heated at 50 °C for 30 min;

[0054] Among them, the volume ratio of ethanol to KH550 is 5:1, the ratio of the mass of carbon material to the total volume of ethanol, KH550, PVP, and carbon material is 1 mg:1 mL, the ratio of the mass of PVP to the total volume of ethanol, KH550, PVP, and carbon material is 2 mg:1 mL, and the mass ratio of pre-oxidized carbon fiber to carbon material is 2:1;

[0055] (3.2) separating the solid and liquid of the system in step (3.1), adding water to the liquid and then ultrasonicating for 30 minutes, then mixing the solid and liquid, heating at 50° C. for 30 minutes, ultrasonicating for 30 minutes, washing, and drying at 60° C. to remove the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber, thereby obtaining a modified carbon fiber;

[0056] The ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:0.5.

[0057] In order to prove the changes in the chemical groups on the surface of carbon fiber before and after chemical grafting, the carbon fiber (carbon fiber precursor, Untreated-CF) in step (1), the pre-oxidized carbon fiber (O-CF) prepared in step (2), and the modified carbon fiber (CNT-CF) finally prepared in step (3) were tested by infrared spectroscopy to evaluate the functional groups on the surface of carbon fiber; Figure 3 As shown in the figure, both the pre-oxidized carbon fiber and the modified carbon fiber are at 3440 cm -1 1635cm -1 The two peaks correspond to the stretching vibration of hydroxyl (AOH) and carbonyl (AC=O), indicating that the surface of the carbon fiber has been successfully oxidized and carboxyl active groups have been introduced. In addition, compared with the pre-oxidized carbon fiber, the modified carbon fiber has a higher absorption peak at 1045cm -1A new peak appears near , which is attributed to Si-O-Si stretching vibration. This result shows that the present invention successfully uses PVP to graft carboxylated MWCNTS onto the surface of carbon fiber.

[0058] The final modified carbon fiber has a single-filament tensile breaking strength of 5 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 58 MPa.

[0059] The carbon fiber (carbon fiber precursor) in step (1) of this embodiment, the pre-oxidized carbon fiber obtained in step (2) and the modified carbon fiber finally obtained in step (3) were subjected to a PA66 microsphere removal test. The results are as follows: Figure 4 As shown; from Figure (a), it can be seen that the surface of the carbon fiber after the microspheres are pulled out is very smooth, and no residual resin fragments can be observed. This is mainly due to the high inertness of the carbon fiber surface, low wettability, and poor bonding with the resin. From Figures (b) and (c), it can be seen that after pulling out, there is a small amount of obvious resin residue on the surface of the pre-oxidized carbon fiber, and the shape of the broken part is relatively irregular compared with the original silk. This is mainly due to the increase in surface activity of the pre-oxidized carbon fiber, the enhanced adhesion to the resin, and the increased wettability. From Figure (d), it can be seen that the residual resin fragments on the surface of the modified carbon fiber after pulling out become more, indicating that the modified carbon fiber has a stronger adhesion to the resin, and the grafting modification of carbon nanotubes really and effectively improves the surface activity of the carbon fiber.

[0060] An application of modified carbon fiber is to compound the modified carbon fiber prepared above with PA66 resin to prepare a composite material.

[0061] Comparative Example 1

[0062] A carbon fiber modification method is basically the same as the carbon fiber modification method in Example 1, except that the same mass of sodium dodecylbenzene sulfonate (SDBS) is used in this comparative example to replace the PVP in Example 1.

[0063] The final modified carbon fiber has a single-filament tensile breaking strength of 4.4 GPa, and its surface morphology is shown in the figure. Figure 5 As shown; the micro-debonding strength between the modified carbon fiber and PA66 resin is 48MPa.

[0064] Compared with Example 1, the single-filament tensile fracture strength of the modified carbon fiber obtained in Example 1 and the interfacial shear strength of the composite material are reduced. This result is unexpected because the dispersion performance of SDBS on carbon materials is better than that of PVP (verified by experiments). In theory, the single-filament tensile fracture strength of the modified carbon fiber obtained in Example 1 and the interfacial shear strength of the composite material should be higher than those in Example 1. However, the fact is just the opposite. The possible reason is that after oxidation of the carbon fiber surface, oxygen-containing groups such as carboxyl and hydroxyl groups will exist, and SDBS is an anionic dispersant. The two will repel each other due to the same charge. Although SDBS can disperse the carbon material well, due to the repulsion of like charges, the grafting effect of SDBS on the surface of pre-oxidized carbon fiber is not ideal.

[0065] Comparative Example 2

[0066] A carbon fiber modification method is basically the same as the carbon fiber modification method in Example 1, except that the same mass of sodium dodecyl sulfate (SDS) is used in this comparative example to replace the PVP in Example 1.

[0067] The final modified carbon fiber has a single-filament tensile breaking strength of 3.9 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 45 MPa.

[0068] Compared with Example 1, the single-filament tensile fracture strength of the modified carbon fiber obtained in Comparative Example 2 and the interfacial shear strength of the composite material are reduced. This result is unexpected because the dispersion performance of SDS on carbon materials is better than that of PVP (verified by experiments). In theory, the single-filament tensile fracture strength of the modified carbon fiber obtained in Comparative Example 2 and the interfacial shear strength of the composite material should be higher than those in Example 1. However, the fact is just the opposite. The possible reason is that after oxidation of the carbon fiber surface, oxygen-containing groups such as carboxyl and hydroxyl groups will exist, and SDS is an anionic dispersant. The two will repel each other due to the same charge. Although SDS can disperse the carbon material well, due to the repulsion of like charges, the grafting effect of SDS on the surface of pre-oxidized carbon fiber is not ideal.

[0069] Example 2

[0070] A carbon fiber modification method, the specific steps are as follows:

[0071] (1) Raw material preparation:

[0072] Carbon fiber;

[0073] K2S2O8 / AgNO3 aqueous solution: composed of K2S2O8, AgNO3 and water, the mass ratio of K2S2O8 to AgNO3 is 20:1, and the concentration of K2S2O8 is 0.1 mol / L;

[0074] Ethanol;

[0075] KH550;

[0076] PVP: degree of polymerization is 50000;

[0077] Carbon material: graphene oxide;

[0078] (2) Preparation of pre-oxidized carbon fibers:

[0079] The carbon fiber was added to a K2S2O8 / AgNO3 aqueous solution and heated in a water bath at 90°C for 75 minutes, then taken out, washed with water, and finally added to ethanol and refluxed at 100°C for 4 hours, taken out, and dried to obtain pre-oxidized carbon fiber. The schematic diagram of its surface morphology is shown in the figure. Figure 1 As shown;

[0080] Among them, the mass ratio of carbon fiber to K2S2O8 / AgNO3 aqueous solution is 1:20;

[0081] (3) Preparation of modified carbon fiber:

[0082] (3.1) Pre-oxidized carbon fiber was added to a mixture of ethanol, KH550, PVP, and carbon material, first ultrasonicated for 45 min, and then heated at 60 °C for 45 min;

[0083] Among them, the volume ratio of ethanol to KH550 is 7:1, the ratio of the mass of carbon material to the total volume of ethanol, KH550, PVP, and carbon material is 5 mg:1 mL, the ratio of the mass of PVP to the total volume of ethanol, KH550, PVP, and carbon material is 4 mg:1 mL, and the mass ratio of pre-oxidized carbon fiber to carbon material is 4:1;

[0084] (3.2) The system of step (3.1) is separated into solid and liquid. Water is added to the liquid and then ultrasonicated for 45 minutes and then the solid and liquid are mixed. Then, the mixture is heated at 60°C for 45 minutes. Then, the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber is removed by ultrasonication for 45 minutes, washing, and drying at 70°C. Thus, the modified carbon fiber is obtained. The schematic diagram of its surface morphology is shown in FIG. Figure 3 As shown;

[0085] The ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:1.

[0086] The final modified carbon fiber has a single-filament tensile breaking strength of 5.1 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 59 MPa.

[0087] An application of modified carbon fiber is to compound the modified carbon fiber prepared above with PA66 resin to prepare a composite material.

[0088] Example 3

[0089] A carbon fiber modification method, the specific steps are as follows:

[0090] (1) Raw material preparation:

[0091] Carbon fiber;

[0092] K2S2O8 / AgNO3 aqueous solution: composed of K2S2O8, AgNO3 and water, the mass ratio of K2S2O8 to AgNO3 is 16:1, and the concentration of K2S2O8 is 0.06mol / L;

[0093] Ethanol;

[0094] KH550;

[0095] PVP: degree of polymerization is 5000;

[0096] Carbon material: carboxylated MWCNTS;

[0097] (2) Preparation of pre-oxidized carbon fibers:

[0098] The carbon fiber was added to K2S2O8 / AgNO3 aqueous solution and heated in a water bath at 80°C for 60 minutes, then taken out, washed with water, and finally added to ethanol and refluxed at 90°C for 5 hours, taken out, and dried to obtain pre-oxidized carbon fiber. The schematic diagram of its surface morphology is shown in Figure 2 As shown;

[0099] Among them, the mass ratio of carbon fiber to K2S2O8 / AgNO3 aqueous solution is 1:30;

[0100] (3) Preparation of modified carbon fiber:

[0101] (3.1) Pre-oxidized carbon fiber was added to a mixture of ethanol, KH550, PVP, and carbon material, first ultrasonicated for 60 min, and then heated at 70 °C for 60 min;

[0102] Among them, the volume ratio of ethanol to KH550 is 9:1, the ratio of the mass of carbon material to the total volume of ethanol, KH550, PVP, and carbon material is 2 mg:1 mL, the ratio of the mass of PVP to the total volume of ethanol, KH550, PVP, and carbon material is 6 mg:1 mL, and the mass ratio of pre-oxidized carbon fiber to carbon material is 6:1;

[0103] (3.2) separating the solid and liquid of the system in step (3.1), adding water to the liquid and ultrasonicating for 60 minutes, then mixing the solid and liquid, heating at 70° C. for 60 minutes, ultrasonicating for 60 minutes, washing, and drying at 80° C. to remove the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber, thereby obtaining a modified carbon fiber;

[0104] The ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:1.5.

[0105] The final modified carbon fiber has a single-filament tensile breaking strength of 5.2 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 60 MPa.

[0106] An application of modified carbon fiber is to compound the modified carbon fiber prepared above with PA66 resin to prepare a composite material.

[0107] Example 4

[0108] A carbon fiber modification method, the specific steps are as follows:

[0109] (1) Raw material preparation:

[0110] Carbon fiber;

[0111] K2S2O8 / AgNO3 aqueous solution: composed of K2S2O8, AgNO3 and water, the mass ratio of K2S2O8 to AgNO3 is 18:1, and the concentration of K2S2O8 is 0.08 mol / L;

[0112] Ethanol;

[0113] KH550;

[0114] PVP: degree of polymerization is 5000;

[0115] Carbon material: graphene oxide;

[0116] (2) Preparation of pre-oxidized carbon fibers:

[0117] The carbon fiber was added to a K2S2O8 / AgNO3 aqueous solution and heated in a water bath at 60°C for 45 minutes, then taken out, washed with water, and finally added to ethanol and refluxed at 120°C for 3 hours, taken out, and dried to obtain pre-oxidized carbon fiber;

[0118] Among them, the mass ratio of carbon fiber to K2S2O8 / AgNO3 aqueous solution is 1:40;

[0119] (3) Preparation of modified carbon fiber:

[0120] (3.1) Pre-oxidized carbon fiber was added to a mixture of ethanol, KH550, PVP, and carbon material, first subjected to ultrasonic treatment for 75 min, and then heated at 80 °C for 75 min;

[0121] Among them, the volume ratio of ethanol to KH550 is 10:1, the ratio of the mass of carbon material to the total volume of ethanol, KH550, PVP, and carbon material is 3 mg:1 mL, the ratio of the mass of PVP to the total volume of ethanol, KH550, PVP, and carbon material is 8 mg:1 mL, and the mass ratio of pre-oxidized carbon fiber to carbon material is 8:1;

[0122] (3.2) separating the solid and liquid of the system in step (3.1), adding water to the liquid and then ultrasonicating for 75 minutes, then mixing the solid and liquid, heating at 80° C. for 75 minutes, ultrasonicating for 75 minutes, washing, and drying at 90° C. to remove the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber, thereby obtaining a modified carbon fiber;

[0123] The ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:2.

[0124] The final modified carbon fiber has a single-filament tensile breaking strength of 5.3 GPa, and the micro-debonding strength between the modified carbon fiber and PA66 resin is 61 MPa.

[0125] An application of modified carbon fiber is to compound the modified carbon fiber prepared above with PA66 resin to prepare a composite material.

Claims

1. A carbon fiber modification method, characterized in that: The pre-oxidized carbon fiber is added to a mixture of ethanol, KH550, PVP and carbon material, first ultrasonicated for 30-75 minutes, then heated at 50-80°C for 30-75 minutes, then solid-liquid separation, water is added to the liquid and mixed evenly, the solid and liquid are mixed, and then heated at 50-80°C for 30-75 minutes, and then the carbon material physically adsorbed on the surface of the pre-oxidized carbon fiber is removed to obtain modified carbon fiber, wherein the pre-oxidized carbon fiber is an oxidized carbon fiber, the carbon material is carboxylated MWCNTS or graphene oxide, the volume ratio of ethanol to KH550 is 5-10:1, the mass ratio of the carbon material to the total volume of ethanol, KH550, PVP and carbon material is 1-5 mg:1 mL, the mass ratio of PVP to the total volume of ethanol, KH550, PVP and carbon material is 2-8 mg:1 mL, and the mass ratio of the pre-oxidized carbon fiber to the carbon material is 2-8:

1.

2. A carbon fiber modification method according to claim 1, characterized in that: The ratio of the volume of water to the total volume of the pre-oxidized carbon fiber, ethanol, KH550, PVP, and carbon material is 1:0.5-2.

3. A carbon fiber modification method according to claim 1, characterized in that: Adding water to the liquid and mixing it evenly means adding water to the liquid and then ultrasonicating it for 30-75 minutes.

4. A carbon fiber modification method according to claim 1, characterized in that: The preparation process of pre-oxidized carbon fiber is as follows: first, add the carbon fiber to a K2S2O8 / AgNO3 aqueous solution and heat it in a water bath at 60-100°C for 45-75 minutes. The K2S2O8 / AgNO3 aqueous solution consists of K2S2O8, AgNO3 and water. Then take it out, wash it with water, and finally add it to ethanol and reflux it at 90-120°C for 3-5 hours. Take it out and dry it to obtain the pre-oxidized carbon fiber.

5. A carbon fiber modification method according to claim 4, characterized in that: In the K2S2O8 / AgNO3 aqueous solution, the mass ratio of K2S2O8 to AgNO3 is 15:1-20:1, and the concentration of K2S2O8 is 0.05-0.1 mol / L; the mass ratio of carbon fiber to the K2S2O8 / AgNO3 aqueous solution is 1:10-40.

6. A modified carbon fiber, characterized in that: The modified carbon fiber is prepared by the carbon fiber modification method as described in any one of claims 1 to 5, the single-filament tensile breaking strength of the modified carbon fiber is 5.0-5.3 GPa, and the micro-debonding strength between the modified carbon fiber and the PA66 resin is 58-61 MPa.

7. The use of a modified carbon fiber as claimed in claim 6, characterized in that: Used to prepare composite materials with PA66 resin.

Citation Information

Patent Citations

  • Preparation method of carbon nano tube loaded carbon fiber

    CN103409985A

  • Method for preparing carbon nanotube grafted glass fiber multiscale reinforcement reinforced polyimide composite

    CN102382319A

  • Carbon fibers and resin composition containing the same

    JP2020169424A